Symptom reduction in advanced cancer from multi-session mindful breathing : randomised controlled study - Tung, Yu Zhen; Diana Ng, Leh Ching; Natalie, Zi Lai; Ang, Chui Munn; Lim, Poh Khuen; Sheriza Izwa, Zainuddin; Lam, Chee Loong; Loh, Ee Chin; Chai, Chee Shee; Tan, Seng Beng (BMJ Publishing Group Ltd., 2025)
Objectives While single-session mindful breathing shows symptom reduction in palliative care, data on multi-session efficacy is lacking. This study aimed to determine the effectiveness of multi-session mindful breathing in reducing symptoms among patients with advanced cancer. Methods Adult patients with advanced cancer who scored ≥4 in at least two or more symptoms based on the Edmonton Symptom Assessment Scale (ESAS) were recruited from January to March 2020 at the University of Malaya Medical Centre, Malaysia. Participants were randomly assigned to receive either four daily sessions of 30 min mindful breathing and standard care (intervention) or standard care alone (control). The outcome measured was the change in the ESAS score after each session. Results 80 patients were recruited and randomised equally into the intervention and control groups. The demographic and clinical characteristics between the two groups were not statistically different. For the intervention group, there were statistically significant reductions in the total ESAS scores following all four sessions of 30min mindful breathing (n1=40: z1=−5.09, p<0.001; z2=−3.77, p<0.001; z3=−4.38, p<0.001; z4=−3.27, p<0.05). For the control group, statistically significant reductions in the total ESAS scores were seen only after sessions 1 and 3 (n2=40: z1=−4.04, p<0.001; z3=−4.53, p<0.001). Conclusions Our result provides evidence that four daily sessions of 30min mindful breathing may be effective in reducing multiple symptoms rapidly in patients with advanced cancer .